Fabrication of chitosan loaded metronidazole nanoparticle for periodontal disease treatment - Mohd Zayi, Nora Azirah; Halim, Lutfi; Harun @ Ismail, Ahmad Fahmi; Mohamad, Mohd Yusof; Arzmi, Mohd Hafiz (2021)
Periodontal disease is a dental infection caused by bacteria that can progress to severe periodontitis, which destroys the connective and alveolar tissues and results in tooth loss. It affects the quality of life of 11.2% of adults worldwide, as well as socioeconomic and healthcare costs. Clinically, guided bone regeneration is used to repair an alveolar bone defect, which is then followed by antibacterial ointment. Metronidazole has been the antibiotic of choice in the treatment of severe periodontitis due to its broad-spectrum activity and efficacy against obligate anaerobes. However, because the administered dose did not sufficiently reach the therapeutic site, the number of follow-up visits has increased. Nanotechnology offers an alternative strategy to overcome drug deficiencies by releasing the drug at the targeted site for an extended period, improving penetration, and preventing drug side effects. In this study, chitosan-loaded metronidazole (CS-MN) nanoparticles were fabricated through the ionic gelation technique with crosslinking agents, sodium thiosulfate. The nanoparticles were analysed and characterized in terms of particle size, polydispersity index, zeta potential, and encapsulation efficiency. The results showed that the nanoparticles produced had a particle diameter of 308 nm, polydispersity index of 0.374, positive zeta potential >30mV, and encapsulation efficiency of 88%. In this study, a nanometre-sized drug with a monodisperse population, ideal zeta potential, and high encapsulated drug content of CS-MN nanoparticles were suitable to be used in nano-systems and local drug delivery in periodontal disease treatment. Further in vitro studies are required to analyse the drug's effectiveness and safety in periodontal bone regeneration.